Mapping the Employee Layoff of Star Hotels in Denpasar City : An Effort to Reduce the Impacts of the Covid-19 Pandemic - Luh Sri Wedaningsih; Nyoman Utari Vipriyanti; Wayan Maba; I GD Yudha Partama (Politeknik Negeri Bali, 2021)
The Covid-19 pandemic has impacted various business sectors including the tourism sector. Hotel industry in Denpasar City has closed its business operations, laid off its employees and terminated their employees. This study was conducted to map the distribution of employees layoff at star hotels in Denpasar City and formulate strategies for star hotels to reduce employee layoff rate due to the Covid-19 pandemic. Eight (8) star hotels in Denpasar City were used as samples based on the data released by Bali Province Manpower and Energy Office in 2020. Questionnaires were distributed to collect data from October to December 2020. This study employed a combination of qualitative and quantitative methods in the forms of qualitative descriptive analysis approach, SWOT analysis and QSPM. The results showed that the largest number of layoffs occurred in the 3-star hotel cluster with an average layoff of 32 percent. Market penetration through optimization of information technology-based promotion tools (IT) is proposed as the main strategy to overcome the problem. The results of this study are expected to provide overviews and recommendations for hotel management in applying this strategy more effectively through professional communication and resource management in order to avoid employee layoffs.